Searches for scalar top and scalar bottom quarks at LEP2 - BARATE, R.; et al. (Institutional Knowledge at Singapore Management University, 1997)
Searches for scalar top and bottom quarks have been performed with data collected by the ALEPH detector at LEP. The data sample consists of 21.7 pb−1 taken at √ s = 161, 170, and 172 GeV and 5.7 pb−1 taken at √ s = 130 and 136 GeV. No evidence for scalar top quarks or scalar bottom quarks was found in the channels ˜t → cχ, ˜t → bℓν˜, and b˜ → bχ. For the channel ˜t → cχ a limit of 67 GeV/c 2 has been set on the scalar top quark mass, independent of the mixing angle between the supersymmetric partners of the left and right-handed states of the top quark. This limit assumes a mass difference between the ˜t and the χ of at least 10 GeV/c 2 . For the channel ˜t → bℓν˜ the mixingangle independent scalar top limit is 70 GeV/c 2 , assuming a mass difference between the ˜t and the ˜ν of at least 10 GeV/c 2 . For the channel b˜ → bχ, a limit of 73 GeV/c 2 has been set on the mass of the supersymmetric partner of the left-handed state of the bottom quark. This limit is valid if the mass difference between the b and the ˜ χ is at least 10 GeV/c 2 .